Event-triggered Sliding Mode Control for light load efficiency improvement in Power Converters. (July 2020) - Rathore, Nupur; Fulwani, Deepak; Rathore, Akshay K.
Abstract: Power converters, operating under fixed switching control, observe a substantial efficiency drop at light load owing to the associated fixed switching losses. To maintain the flat efficiency curve, varying the switching frequency depending on the load has been explored in the literature as a better alternative to fixed-frequency operation. This paper presents Event-triggered Sliding Mode Control (ETSMC) based variable frequency modulation scheme for power converters. The presented strategy leverage converter dynamics to execute control signal. This need-based switching technique ensures reduced switching losses and hence improved efficiency, without compromising on performance. Widely adopted switching reduction technique of Hysteresis modulation based SMC is established as a special case of ETSMC, thus highlighting the proposed scheme's generic nature. The scheme is demonstrated on an isolated half-bridge converter. Simulations, as well as experimentation results, are included to support the theory. Highlights: This is the first work to propose Event-triggered Sliding mode control (ETSMC) to improve low load efficiency in power converter. Load adaptive variable frequency operation is achieved by leveraging system dynamics to adapt the sliding band size. The proposed scheme is generic in nature and HM -SMC is presented as a special case of ETSMC with memory less event-triggered mechanism. Efficiency is maintained and the voltage is regulated for a wide range of loads.